Congruent geographic variation in saccular otolith shape across multiple species of African cichlids - Bose, Aneesh P. H.; Zimmermann, Holger; Winkler, Georg; Kaufmann, Alexandra; Strohmeier, Thomas; Koblmüller, Stephan; Sefc, Kristina M. (My University, 2020)
The otoliths of teleost fishes exhibit a great deal of inter- and intra-species shape variation. The ecomorphology of the saccular otolith is often studied by comparing its shape across species and populations inhabiting a range of environments. However, formal tests are often lacking to examine how closely variation in otolith shape follows the genetic drift of a neutral trait. Here, we examine patterns of saccular otolith shape variation in four species of African cichlid fishes, each sampled from three field sites. All four species showed the greatest level of otolith shape variation along two principal component axes, one pertaining to otolith height and another to the prominence of an anterior notch. Fish collected from the same site possessed similarities in saccular otolith shape relative to fish from other sites, and these 'site-difference' signatures were consistent across species and observable in both sexes. Sex-differences in saccular otolith shape differed in magnitude from site to site. Population differences in saccular otolith shape did not covary with neutral genetic differentiation between those populations. Otolith height, in particular, displayed large site similarities across species, weak correlation with neutral genetic variation, and strong sex differences, collectively suggesting that otolith shape represents a selectively non-neutral trait.
Keywords: 570